Autorganizzazione comunitaria e produzione - Giuseppe Caridi (Scienze del Territorio, 2019)
This paper intends to explore the issue of the evident increase of experiences that aim to give centrality to processes of community self-organisation. A possible way to reflect on this trend can be sought in the strong and growing attention given to the theme of commons. The author argues that community self-organisation represents the reference point and the starting instrument for the production and reproduction of commons. The paper takes two main aspects into consideration. The first one highlights how the need for a rethinking of the dominant conception of associated living can only pass through a strengthening of the non-institutional sphere and of its instituting dynamics. Such a perspective expands the scope of the discussion with regards to processes of self-organisation as to the potentiality and the role of commons. The second one considers five specific design options which prove useful for identifying the causal links between community self-organisation and production of commons. These options can be traced back to the forms: i) of collaboration between citizens and administrations; ii) of the reconversion connected to the patrimonial contrast to organised crime; iii) of the pluralisation connected to reception and emergency; iv) of the regeneration connected to reuse and sharing of open spaces and of architectural artefacts; v) of the disputes related to squatting for housing purposes and those related to the cultural and art scene.